2014
DOI: 10.1115/1.4026215
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of the Transient Behavior of an Industrial Power Plant Gas Turbine

Abstract: This study deals with modeling and simulation of the transient behavior of an Industrial Power Plant Gas Turbine (IPGT). The data used for model setup and validation were taken experimentally during the start-up procedure of a single-shaft heavy duty gas turbine. Two different models are developed and compared by using both a physics-based and a black-box approach, and are implemented by using the MATLAB tools including Simulink and Neural Network toolbox, respectively. The Simulink model was constructed based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 30 publications
0
27
0
2
Order By: Relevance
“…A Simulink model to predict the transient response of an industrial power plant gas turbine (IPGT) was reported by Asgari et al [29]. The Simulink Model was constructed from thermodynamic and energy equations.…”
Section: Introductionmentioning
confidence: 99%
“…A Simulink model to predict the transient response of an industrial power plant gas turbine (IPGT) was reported by Asgari et al [29]. The Simulink Model was constructed from thermodynamic and energy equations.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have applied various regression methods and other machine learning techniques to CCGT performance prediction [9] and fault detection [10]. The application of artificial neural networks (ANN) as reliable alternatives for various simulation control modelling and fault detection applications for CCGT is now well established [11][12][13]. Other machine learning methods including Least Squares Support Vector Machines (LSSVM) [14] and adaptive neuro-fuzzy inference system (ANFIS) [15] are also applied for modelling and controlling GT.…”
Section: Introductionmentioning
confidence: 99%
“…They also defined a novel performance function for better analysis of quick transients and could design an accurate and efficient tool for simulations that could also be used for diagnosis of gas turbines. Asgari et al [8] performed a series of studies on the start-up phase of a heavy-duty industrial gas turbine using neural network approach implemented in MATLAB. Both NARX and Simulink models were capable of appropriate prediction but not the turbine behavior during the cold start-up phase.…”
Section: Introductionmentioning
confidence: 99%